Varietal Evaluation and 30 kDa Protein Studies in Local Bitter Gourd (Momordica charantia L.) - Charan Ditchaiwong; Prachya Kongtawelert; Surapol Natakankitkul; Manoch Tongjiem; Maneechat Nikornpun (Agriculture and Natural Resources, 2002)
Twelve accessions of local bitter gourds were tested in comparison with a cultivated bitter gourd at Phichit Horticultural Research Center in summer 2000. Botanical and horticultural characteristics of leaf, pistillate flower, staminate flower, fruit and seeds were recorded. Ripe fruit yield of the accessions ranged from 3,227 to 6,912 kg/ha. Yield was not significantly different among the accessions but showed high variation in protein levels in extraction from endosperm. The partial protein powder ranged from 104.33 to 208.67 mg/5 g of endopsperm while the specific activity protein at 30 kDa evaluated by the polyacrylamide gel electrophoresis (PAGE) method ranged from 104.86 to 265.42 μg/5g of endosperm. One specific accession (No.16) gave the highest level of the specific activity protein at 30 kDa, however, it gave high level of the partial protein powder, 168.33 μg/5g. Contradictory, the other accession (No.11) which had more or less the same level of total protein as the mentioned accession, had rather low level of the specific activity protein at 30 kDa, 149.96 μg/5g of endosperm.